Las Normas Internacionales de Información Financiera (NIIF) para pequeñas y medianas empresas (PYMES) sección 13 inventarios y su incidencia en la Gestión Financiera de la ferretería Balcazar ubicada en la provincia de Orellana, cantón Joya de los Sachas en el periodo 2017 – 2018 - Naranjo Chiguano, Diana Lorena (2019)
This research project was developed in the "Balcazar" hardware store with the purpose of carrying out an assessment of inventories and financial management, for which the research topic was raised: INTERNATIONAL FINANCIAL INFORMATION REGULATIONS (IFRS) FOR SMALL AND MEDIANAS EMPRESAS (PYMES) SECTION 13 INVENTORIES AND THEIR INCIDENCE IN THE FINANCIAL MANAGEMENT OF THE "BALCAZAR" HARDWARE LOCATED IN THE PROVINCE OF ORELLANA, CANTÓN JOYA DE LOS SACHAS IN THE PERIOD 2017 - 2018, taking into account that the main problem is like application of the IFRS for SMEs section 13 inventories has an impact on the financial management of the hardware store, for this a survey, interview and documentary observation format was made, through which it was determined that they do not apply the IFRS for SMEs section 13 inventories , for which the main objective was to propose an inventory valuation guide through the application of International Financial Reporting Standards (IFRS) for Small and Medium Enterprises (SMEs) section 13 inventories and their impact on financial management. The theoretical framework is fundamental because it provides key definitions for a better understanding and development of this research, the legal framework is paramount because it regulates the commercial activity of the hardware store. For the development of this research the analytical, inductive, deductive and historical method was used. The first method was used to perform an analysis and interpretation about the results of the survey, interview and documentary observation, the second method was used to analyze the problems about inventories and financial management, the third method allowed to draw conclusions from general to particular about inventories and financial management and the last method was used to conduct the background and find the solution to the research problem. Keywords: Inventories, Inventory Control, IFRS, SMEs, Financial Management, Inventory Valuation Guide.